Investigating Emergency Nurses’ Awareness on the Differentiation Between Acute Methanol and Ethanol Intoxication - Memarian, Azadeh; Mostofizadeh, Romina; Aghakhani, Kamran; Rismantab Sani, Sahar; Abdolkarimi, Leyla; Soltani, Siamak (International Journal of Medical Toxicology and Forensic Medicine, 2021)
Background: Alcohol intoxication is among the leading and preventable causes of death, disability, and injury in numerous societies. Ethanol and methanol are the most commonly used types of alcohol. Increasing nurses’ awareness about the difference between intoxication with these two alcohol types will prevent the occurrence of dangerous and deadly complications of intoxication. We investigated the awareness of the nurses respecting the difference between acute methanol and ethanol intoxication in clinical manifestations, diagnosis, and treatment. Methods: A cross-sectional study was performed in 2020 on the emergency nurses from two educational hospitals. A total of 100 nurses participated in this study. The data collection tool was a researcher-made questionnaire, including demographic characteristics and questions concerning the identification and differentiation of acute methanol from ethanol intoxication. Moreover, the obtained data were analyzed using SPSS v. 20 at the significance level of P<0.05. Results: The present research results suggested that 21% of the examined nurses had a low level of awareness (<7) and 79% had a moderate level of awareness (8-13). The mean score of awareness was measured as 8.71 (range: 2-12). Nurses’ awareness was not related to age, gender, the duration of working experience, and educational level (P>0.05). Conclusion: The awareness of nurses regarding alcohol poisoning is moderate. Due to the importance of differentiating ethanol from methanol toxicity, considering the outcomes of the patients, nurses’ awareness should be increased.